IDENTIFICATION OF INSECTS ON LONG BEA CLANTS ( Vigna unguiculata ) IN KOR HILL, MARANG, TERENGGANU - Adha Tanjung, Ferdi; Atminingsih, Atminingsih; Hashim, Nur Aida (Institute of Computer Science (IOCS), 2024)
Long beans are a type of vegetable that is very popular among the people of Indonesia and the world. People around the world call it Yardlong Beans/Cow Peas. Pests are plant destroyers that can reduce the growth and production of cultivated plants, which can cause crop failure, thereby causing large losses for farmers. Pests that attack long bean plants are grasshoppers ( Oxya sp ., Fam. Acrididae), green leafhoppers ( Empoasca spp ., Fam. Cicadellidae), leaf caterpillars (Fam. Pyralidae), pod borers (Fam. Pyralidae), aphis lice ( Aphis craccivora , Fam. Aphididae), green ladybugs ( Nezara viridula , Fam. Pentatomidae), and whitefly ( Bemisia tabaci, Fam. Hemiptera). The aim of this research was to determine the diversity of insects on long bean plants ( Vigna sinensis L. ) in Kor Hill, Marang, Terengganu. The research method was carried out using qualitative methods, this research collected insects on long bean cultivation plants. This research examines insect body parts, description and classification. The results of this research were fruit flies ( Bactrocera dorsalis ), green bottle flies ( Lucilia sericata ), red imported fire ants ( Solenopsis invicta ), koksi beetles ( Epilachna admirabilis ), Sangit grasshoppers ( Leptocorisa acuta ) and grasshoppers ( Valanga nigricornis ).